The Strange Voyage and Adventures of Domingo Gonsales, to the World in the Moon - Godwin, Francis, 1562-1633 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Strange Voyage and Adventures of Domingo Gonsales, to the World in the Moon" by Francis Godwin is a work written in the late 1620s and published posthumously in 1638. This pioneering tale of lunar exploration follows Domingo Gonsales, a Spanish exile who discovers that trained birds can carry him through the air. When his ship is attacked, he escapes skyward$1 (Bonly to find himself journeying to the Moon, where he encounters a utopian society of tall Christians and discovers magical stones with extraordinary properties before returning to Earth. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Man_in_the_Moone
Release date is 2014-08-15
Produced by Marc D'Hooghe (Images generously made available by the Internet Archive)
Keywords: Moon -- Fiction; Voyages, Imaginary -- Early works to 1800